Who says that CAD/CAM cannot be done for children? - Miss Gizem AKKUŞ; A/Prof Didem Oner Ozdas; DDS Serra Küçükkılıç; Prof. Dr. Ali Murat Kökat (Elsevier, 2023)
Introduction: CAD/CAM stands for computer-aided design and computer-aided manufacturing. Computer-aided applications have started to be used in all fields of dentistry. Shortening the time spent in the chair, laboratory procedures, and increasing the success of the treatment. For the use in children due to its high cost, it is quite beneficial applying permanent teeth. Case Description: Two case presentations will be discussed, both cases are systemically health female patients. Case 1 is 13-year-old with lost upper right lateral incisor due to trauma. A maryland bridge has been planned for protecting space and aesthetic satisfaction. After taking digital impression, maryland bridge has been milled from a zirconium (InCoris TZI, Dentsply-Sirona). It has been followed-up for 15 months.Case 2 is 11-year-old patient. After the root canal treatment, it has been decided to perform an endocrown with CAD/CAM. After taking digital impression, endocrown milled from lithium disilicate block (IPS-emax-press-IVOCLAR) and cemented. It has been followed-up for 13 months.For cementation self-adhesive dual cure(SET-PP, SDI, Australia) was used for both of cases.Same cementation procedures was used in both cases. Discussion: The use of prosthetic restorations in children is not common due to the difficulty in conventional impression taking and lack of cooperation from children. Using of CAD/CAM makes easier both taking impression and patient cooperation. Provide better adaptation. Conclusion/Clinical Significance: CAD/CAM applications are highly valuable in pediatric patient due to the ease of tolerating impression method and their ability to provide the best possible aesthetics and function for permanent teeth.